A Suicide Gene Therapy Combining the Improvement of Cyclophosphamide Tumor Cytotoxicity and the Development of an Anti-Tumor Immune Response - Touati, Walid; Tran, Thi; Seguin, Johanne; Diry, Monique; Flinois, Jean-Pierre; Baillou, Claude; Lescaille, Geraldine; Andre, Francois; Tartour, Eric; M. Lemoine, Francois; Beaune, Philippe; de Waziers, Isabelle (Current Gene Therapy, 2014)
Gene-directed enzyme prodrug therapy (GDEPT) consists in targeted delivery to tumor cells of a suicide gene responsible for in situ conversion of a prodrug into cytotoxic metabolites. One of the major limitations of this strategy in clinical application was the poor prodrug activation capacity of suicide gene. We built a highly efficient suicide gene capable of bioactivating the prodrug cyclophosphamide (CPA) by fusing a CYP2B6 triple mutant with NADPH cytochrome P450 reductase (CYP2B6TM-RED). Expression of this fusion gene via a recombinant lentivirus (LV) vector converted resistant human (A549) and murine (TC1) pulmonary cell lines into CPA-susceptible cell lines. We tested the efficiency of our GDEPT strategy in C57Bl/6 immunocompetent mice, using TC1 cells expressing the HPV-16 E6/E7 oncoproteins. In mice bearing tumors composed only of TC1-CYP2B6TM-RED cells, four CPA injections (140 mg/Kg once a week) completely eradicated the tumors for more than two months. Tumors having only 25% of TC1-CYP2B6TM-RED cells were also completely eradicated by five CPA injections, demonstrating a major in vivo bystander effect. Moreover, surviving mice were rechallenged with parental TC1 cells. The tumors regressed spontaneously 7 days after cell inoculation or grew more slowly than in control naive mice due to a strong immune response mediated by anti-E7CD8+T cells. These data suggest that combining the CYPB6TM-RED gene with CPA may hold promise as a highly effective treatment for solid tumors in humans.
Keywords: Cytochrome P450 2B6